A moral history of seizures: reported causes of seizures in the nineteenth century - Lima, Márcio Pinheiro; Yacubian, Elza Márcia Targas (Arquivos de Neuro-Psiquiatria, 2025)
In the nineteenth century, neurology was in its infancy as an organized medical specialty. At that time, seizures were often attributed, under the guise of scientific explanations, to moral causes or behaviors. The medical literature from this period contains references to poor parental care as a cause of epilepsy and descriptions of seizures being inherited alongside other undesirable traits. Temperance was praised, while gluttony was associated with epileptic fits. Unwanted sexual behaviors, such as masturbation, were also considered a risk factor for seizures. Women were thought to be more prone to epilepsy due to their behaviors and emotional disposition. These accounts illustrate the interplay between neurological science and the prevailing social norms of the era.
Keywords: Epilepsy; History, 19th Century; History of Medicine; Neurology